Sexual activity increases the number of newborn cells in the accessory olfactory bulb of male rats - Portillo, Wendy; Unda, Nancy M.; Camacho, Francisco J.; Sanchez, Maria; Corona, Rebeca; Arzate, Dulce M.; Díaz, Néstor F.; Paredes, Raúl G. (Frontiers in Neuroanatomy, 2012)
In rodents, sexual behavior depends on the adequate detection of sexually relevant stimuli. The olfactory bulb (OB) is a region of the adult mammalian brain undergoing constant cell renewal by continuous integration of new granular and periglomerular neurons in the accessory (AOB) and main (MOB) olfactory bulbs. The proliferation, migration, survival, maturation, and integration of these new cells to the OB depend on the stimulus that the subjects received. We have previously shown that 15 days after females control (paced) the sexual interaction an increase in the number of cells is observed in the AOB. No changes are observed in the number of cells when females are not allowed to control the sexual interaction. In the present study we investigated if in male rats sexual behavior increases the number of new cells in the OB. Male rats were divided in five groups: 1) males that did not receive any sexual stimulation, 2) males that were exposed to female odors, 3) males that mated for 1 h and could not pace their sexual interaction, 4) males that paced their sexual interaction and ejaculated 1 time and 5) males that paced their sexual interaction and ejaculated 3 times. All males received three injections of the DNA synthesis marker bromodeoxyuridine at 1h intervals, starting 1h before the beginning of the behavioral test. Fifteen days later, males were sacrificed and the brains were processed to identify new cells and to evaluate if they differentiated into neurons. The number of newborn cells increased in the granular cell layer (also known as the internal cell layer) of the AOB in males that ejaculated one or three times controlling (paced) the rate of the sexual interaction. Some of these new cells were identified as neurons. In contrast, no significant differences were found in the mitral cell layer (also known as the external cell layer) and glomerular cell layer of the AOB. In addition, no significant differences were found between groups in the MOB in any of